Association analysis of differential expression of beta defensins with mastitis in indicine dairy cattle - Gurao, Ankita; Kataria, Ranjit Singh; Singh, Ravinder; Kumar, Ravi D; Mishra, Shailendra Kumar; Kashyap, Sudhir Kumar (Indian Journal of Dairy Science, 2018)
Apart from being a bacterial infection, the intra-mammary inflammation during bovine mastitis is a multifactorial attribute. The hallmark events during the inflammation include an increased in-flow of leucocytes, which release a range of inducible defenses comprising beta defensins such as LAP and bovine neutrophil beta defensin-4 (BNBD4), well associated with milk traits and mastitis. The increased expression of these peptides is therefore evident in peripheral blood mononuclear cells. Since there are no reports on expression of LAP and BNBD4 in indigenous cattle breeds, the present study has focused on generating the expression profiles of these beta defensins in clinical mastitis affected and non-affected healthy indigenous Tharparkar cattle. The results indicated a significant increase in expression of LAP and beta BNBD4 in PBMCs of mastitis animals and thereby established the important role of defensins in mastitis and PBMCs as the sample source to predict these markers for their expression level in infected and healthy cattle.